2018
DOI: 10.1111/aogs.13453
|View full text |Cite
|
Sign up to set email alerts
|

Impact of residual disease on overall survival in women with Federation of Gynecology and Obstetrics stage IIIB‐IIIC vs stage IV epithelial ovarian cancer after primary surgery

Abstract: Our results confirm the positive prognostic impact of both complete cytoreduction and residual disease ≤1 cm in stages IIIB-IIIC as well as stage IV epithelial ovarian cancer. Women with stage IV do benefit from cytoreductive surgery and should be considered for primary debulking surgery, if residual disease = 0 can initially be expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Indeed, a 10% increase in CCS rate, increased median survival by 1.9 months (18). However, it is sometimes difficult to compare data from literature as the definition of CCS varies according to studies, that often define CCS as residual tumor of less than 1 cm (4,9,15,(19)(20)(21). In our study, CCS was not defined by a residual tumor less than 1 cm but by absence of residual tumor (CC0), limiting the biases associated to this factor.…”
Section: Discussionmentioning
confidence: 82%
“…Indeed, a 10% increase in CCS rate, increased median survival by 1.9 months (18). However, it is sometimes difficult to compare data from literature as the definition of CCS varies according to studies, that often define CCS as residual tumor of less than 1 cm (4,9,15,(19)(20)(21). In our study, CCS was not defined by a residual tumor less than 1 cm but by absence of residual tumor (CC0), limiting the biases associated to this factor.…”
Section: Discussionmentioning
confidence: 82%
“…There is an ongoing debate whether women with Stage IV disease should be offered PDS or IDS, and if they benefit from achieving intra‐abdominal R0 despite their extra‐abdominal metastases. Several studies have shown an increase in OS when achieving R0 after PDS in Stage IV EOC 6–8 . However, similar OS has been observed when randomizing EOC groups for PDS followed by chemotherapy or IDS in Stage IIIC–IV EOC 9 .…”
Section: Introductionmentioning
confidence: 70%
“…However, in 2010 the Gynaecological Cancer Inter-Group defined 'optimal' as having no visible residual tumour nodules, i.e. complete macroscopic resection (since microscopic disease remains in the majority of patients) (Stuart 2011), which has been shown to result in better survival than near-optimal (< 1 cm) and suboptimal cytoreduction (> 1 cm) and to be a better predictor of survival (Bookman 2009;Chang 2013;du Bois 2009;Sørensen 2019;Wimberger 2010). While there is now less controversy about the prognostic importance of maximum cytoreduction, there remains divided opinion about the e ects of any remaining residual disease a er UDS or IDS and about what attempts should be made for maximal e orts at debulking.…”
Section: Description Of the Surgical Interventions And Residual Disease As A Prognostic Factormentioning
confidence: 99%